EKSISTENSI ISTILAH TEKNOLOGI INFORMASI PADA MAHASISWA: PERWUJUDAN BAHASA INDONESIA SEBAGAI PENGHELA IPTEKS - Puji Siti Fauziah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This research is based on the lack of knowledge and use regarding the equivalent of Indonesian words contained in the term information technology that should be mastered in the era of globalization. In the era of globalization, the existence of Indonesian has begun to be shifted with the presence of foreign terms that have emerged, especially in the advancement of information technology that has penetrated rapidly. This, causes that the progress of science and technology influences the development of the Indonesian language. For this reason, Indonesian language as a drawer or deterrent to science can create and form new terms, so that it is no longer a foreign term that will often be used. In addition, science and technology is a driving force for developments in other fields of science. So the use of foreign terms means not having pride in using Indonesian. As for the purpose of this study, researchers wanted to know how the existence of the term information technology and its use as an embodiment of the Indonesian language became a science and technology critic for Indonesian language and literary education students. This research uses descriptive qualitative method that describes data and facts in the form of descriptions obtained through questionnaires. The research sample was conducted on 20 Indonesian language and literary education students of IKIP Siliwangi. The results of this study, show that there are 11 terms that have been known and are commonly used by students and there are 9 terms that are unknown and rarely used by students.